Tunability of Triangular SRR and Wire Strip (TSRR-WS) Metamaterial at THz. (24th April 2014) - Dawar, Parul; De, Asok
Abstract : This paper adumbrates a novel tunable metamaterial consisting of triangular split ring resonator (TSRR) and wire strip (WS) at THz frequency. Ansoft high frequency structure simulator (HFSS) has been used to design and analyse the metamaterial having Rogers RT/duroid 5870 (ε r = 2.33) and FR4 (ε r = 4.4) as substrate material. Nicolson Ross Weir (NRW) method has been used to retrieve the material parameters from transmission and reflection coefficient. 4% maximization has been obtained in the location of the negative region (or resonance frequency for permeability) by using FR4 with 0.75 μ m instead of 1.25 μ m as substrate thickness. In addition, 18% minimization has been achieved by using FR4 with 0.25 μ m instead of RT/duroid 5870 substrate with the same thickness. Tunability has been proved by showing dependence of resonant frequency over the substrate thickness and substrate material.